ANALISIS PENERAPAN FUNGSI-FUNGSI MANAJEMEN PADA KANTOR KECAMATAN MAKALE KABUPATEN TANA TORAJA - Althon K.Pongtuluran; Abedneigo Carter Rambulangi (Journal of Management Small and Medium Enterprises (SMEs), 2017)
This research was conducted to find out wheter District Office of Makale has executed ManagementFunctions. Based on the results of the research, the Management Functions in the District Office ofMakale still need improvements. Because it is encountered implementation of centralized in oneline. It has not spread and not coordinated well in accordance with the Tasks, Functions and Stapleeach Head of Section. Methods of analysis was used Qualitative Analysis Method.Keywords : Management Functions